Review of Coelostoma of the Indian subcontinent (Coleoptera: Hydrophilidae) Part 1: Coelostoma s. str. and Holocoelostoma - Sheth, Sayali D.; Ghate, Hemant V.; Fikáček, Martin (European Journal of Taxonomy, 2020)
Species of the genus Coelostoma Brullé, 1935 belonging to the subgenera Coelostoma s. str. and Holocoelostoma Mouchamps, 1958 from the Indian subcontinent are revised. Six species of Coelostoma s. str. and two species of Holocoelostoma are recognized, of which two are described as new: C. (Coelostoma) lyratum sp. nov. (India: Maharashtra) and C. (Coelostoma) nostocinum sp. nov. (India: Maharashtra, Goa, Karnataka, Kerala). Coelostoma (Coelostoma) fallaciosum Orchymont, 1936 and C. (Coelostoma) vividum Orchymont, 1936 were recorded for the first time from India and Bangladesh, respectively. Lectotypes are designated for C. aeneolum Régimbart, 1903 and Hydrobius stultus Walker, 1858. The previously confusing situation with Coelostoma (Holocoelostoma) stultum (Walker, 1858) and C. (Holocoelostoma) bhutanicum Jayaswal, 1972 is clarified based on new material of both species from India. Coelostoma sulcatum Pu, 1963 from China is removed from the synonymy of C. stultum and considered as a likely synonym of C. bhutanicum, a status which needs to be confirmed by a detailed study of type specimens. All species are (re)described and illustrated. Diagnosis of the subgenera of Coelostoma are modified in order to accommodate the species of the Indian subcontinent, resulting in narrowing down the concept of Coelostoma s. str. and widening the concept of Lachnocoelostoma Mouchamps, 1958.